2022
DOI: 10.3389/fpsyt.2022.833865
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Regression on the Heterogenous Factors Contributing to the Prevalence of Mental Health Symptoms During the COVID-19 Crisis Among Healthcare Workers

Abstract: ObjectiveThis paper used meta-regression to analyze the heterogenous factors contributing to the prevalence rate of mental health symptoms of the general and frontline healthcare workers (HCWs) in China under the COVID-19 crisis.MethodWe systematically searched PubMed, Embase, Web of Science, and Medrxiv and pooled data using random-effects meta-analyses to estimate the prevalence rates, and ran meta-regression to tease out the key sources of the heterogeneity.ResultsThe meta-regression results uncovered sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…Likewise, it was higher than the comprehensive prevalence of depression (21.7%) among healthcare workers in 21 countries reported in the meta-analysis report by Li et al ( 54 ). The prevalence of anxiety (28.6%) among healthcare workers in China during the COVID-19 pandemic reported in our study was close to the prevalence of anxiety (29.0%) among front-line medical staff in a separate meta-analysis in China ( 53 ). However, it was higher than the combined prevalence of anxiety (23.0%) among front-line medical staff in Southeast Asia ( 52 ) and the combined prevalence of anxiety (22.1%) among healthcare workers covering 21 countries ( 54 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Likewise, it was higher than the comprehensive prevalence of depression (21.7%) among healthcare workers in 21 countries reported in the meta-analysis report by Li et al ( 54 ). The prevalence of anxiety (28.6%) among healthcare workers in China during the COVID-19 pandemic reported in our study was close to the prevalence of anxiety (29.0%) among front-line medical staff in a separate meta-analysis in China ( 53 ). However, it was higher than the combined prevalence of anxiety (23.0%) among front-line medical staff in Southeast Asia ( 52 ) and the combined prevalence of anxiety (22.1%) among healthcare workers covering 21 countries ( 54 ).…”
Section: Discussionsupporting
confidence: 81%
“…Our results show that the prevalence of depression (55.3%) among healthcare workers in China during the COVID-19 pandemic was higher than in some other meta-analyses and epidemiological surveys during the pandemic. For example, it was much higher than the comprehensive prevalence of depression among front-line medical staff during the outbreak of COVID-19 in Spain (33.0%) ( 51 ), Southeast Asia (14.0%) ( 52 ), and a separate meta-analysis from China (32.0%) ( 53 ). Likewise, it was higher than the comprehensive prevalence of depression (21.7%) among healthcare workers in 21 countries reported in the meta-analysis report by Li et al ( 54 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, office days were positively associated with job and life satisfaction among older colleagues, suggesting that younger healthcare staff who did not work many days and senior healthcare staff who worked more days are the most mentally vulnerable groups ( 44 , 46 ). As revealed by the meta-regression analysis by Chen et al ( 12 ), frontline healthcare workers suffered more from mental symptoms than general healthcare workers, and PTSD had the highest prevalence rates in both groups among all mental health symptoms examined.…”
Section: Discussionmentioning
confidence: 93%
“…While the present analyses mainly focused on nurses and nursing experiences during the first phase of the pandemic, it does not emphasize the mental issues caused by the long-lasting overload. The Chen et al ( 12 ) meta-analysis is interesting in this context, which found that the high rate of symptoms such as anxiety, depression, distress, or insomnia strongly affected the general population and healthcare professionals. Despite the difficult and stressful situation they were living, nurses and nursing assistants who participated in this study attempted to cope with their experiences.…”
Section: Discussionmentioning
confidence: 99%